Older Adult Insights for Age Friendly Environments, Products and Service Systems - SHORE, Linda; KIERNAN, Louise; EYTO, Adam de; BHAIRD, Deirbhile Nic A; CONNOLLY, Anne; WHITE, P J; FAHEY, Tracy; MOANE, Siobhan (Design and Technology Education: An International Journal, 2018)
The environments we grow old in present a challenge to be adaptive to our changing needs and limitations. Environments, in the context of this paper, are the spaces, products and product service systems that we engage with, alone or with others, within and outside the home. A design coalition (Manzini, 2015) was generated between a number of academic Institutions and ISAX (Ireland Smart Ageing Exchange) an ‘ageing think tank’ organisation in Ireland. The intention of this coalition was to generate awareness of needs requirements for age friendly environments and to provide an example of how participatory design research can inform innovation in business and policy development at a local and state level. A five-week study was conducted using design and ethnographic methods with twenty-two older adult participants (age range 69 – 80). The themes of study were identified as: mobility, public spaces, safety, social engagement, services & facilities. Cultural probes, semi-structured interviews and user observation, by both researchers and older adult participants, were used as methods to identify the unmet needs of participants within the sample group. A Co-Design Symposium (http://info.isax.ie/national-co-design-symposium) was held during June 2016 as an opportunity to demonstrate to a wider stakeholder audience the needs identified from this study. This Symposium was attended by over 100 people of various backgrounds (town planners, architects, transport experts, retailers, builders, health and other service providers). The older adult participants and designers (staff and researchers from the School of Design at the University of Limerick, IT Carlow, Limerick Institute of Technology and Limerick School of Art & Design) were placed within teams of ten. The research was presented using audio/visual presentation as well as artefacts from the fieldwork, completed diaries, scrapbooks, storyboards etc. Solutions were worked on, and delivered at the end of the day. This Symposium has impacted positively whereby policy makers in local government have invited ISAX to further discuss research outcomes and the needs of older adults as a means to develop access areas in and around Limerick City. This paper outlines in further detail the design research methods used, and the benefits through design education Student/ Researcher /Stakeholder collaboration by application ‘in the ‘field’ and displays the effectiveness of design coalitions in influencing and affecting change and insight into policy. It highlights how co-design collaborations can impact and generate design solutions that improve day to day experiences.